2007
DOI: 10.1038/ng2038
|View full text |Cite
|
Sign up to set email alerts
|

IFT80, which encodes a conserved intraflagellar transport protein, is mutated in Jeune asphyxiating thoracic dystrophy

Abstract: Jeune asphyxiating thoracic dystrophy, an autosomal recessive chondrodysplasia, often leads to death in infancy because of a severely constricted thoracic cage and respiratory insufficiency; retinal degeneration, cystic renal disease and polydactyly may be complicating features. We show that IFT80 mutations underlie a subset of Jeune asphyxiating thoracic dystrophy cases, establishing the first association of a defective intraflagellar transport (IFT) protein with human disease. Knockdown of ift80 in zebrafish… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
256
2
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 310 publications
(276 citation statements)
references
References 14 publications
14
256
2
4
Order By: Relevance
“…We recently showed that mutations in a core intraflagellar transport (IFT) gene, IFT80, cause Jeune syndrome, a ciliopathy featuring skeletal dysplasia, renal cysts, polydactyly and situs inversus [6]. The zebrafish morphant showed cystic kidneys, random body situs (our unpublished data) and a down-turned body-axis; all features reminiscent of bona fide ciliary mutants.…”
Section: Resultsmentioning
confidence: 83%
“…We recently showed that mutations in a core intraflagellar transport (IFT) gene, IFT80, cause Jeune syndrome, a ciliopathy featuring skeletal dysplasia, renal cysts, polydactyly and situs inversus [6]. The zebrafish morphant showed cystic kidneys, random body situs (our unpublished data) and a down-turned body-axis; all features reminiscent of bona fide ciliary mutants.…”
Section: Resultsmentioning
confidence: 83%
“…IFT172 and IFT80 are both predicted to contain two N‐terminal WD40 β‐propeller domains followed by α‐solenoid structure akin to the domain architecture observed for coatomer subunits (van Dam et al , 2013). Mutations in IFT172 and IFT80 were reported to result in skeletal pattering defects (Beales et al , 2007; Halbritter et al , 2013), and the two components interact genetically (Halbritter et al , 2013) albeit not physically in sucrose gradients (Lucker et al , 2005). We observed no direct interaction between IFT172 and IFT80 in SEC (Appendix Fig S2A and B).…”
Section: Resultsmentioning
confidence: 99%
“…115 Mutations in IFT80, another IFT complex B protein, cause the skeletal ciliopathy asphyxiating thoracic dystrophy (ATD, also known as Jeune syndrome) in humans, a condition that involves retinal degeneration. 121 Zebrafish ift80 morphants exhibit defects in photoreceptor OS formation and photoreceptor death 122 but hypomorphic Ift80 mutations in mice (human mutations associated with ATD are hypomorphic) have normal retinas at P21, although retinal degeneration may occur later.…”
Section: Intraflagellar Transport In the Photoreceptor Axoneme And Inmentioning
confidence: 99%